Exercise and dietary interventions in the management of diabetic cardiomyopathy: mechanisms and implications - Ling Zhong; Xiaojie Hou; Yan Tian; Xianghui Fu (Cardiovascular Diabetology)
Abstract The global prevalence of diabetes is rapidly increasing, significantly raising the risk of various cardiovascular diseases. Among these, diabetic cardiomyopathy (DCM) is a distinct and critical complication characterized by ventricular hypertrophy and impaired myocardial contractility, ultimately progressing to heart failure and making it a leading cause of mortality among diabetic patients. Despite advances in pharmacological therapies, the effectiveness of managing cardiac dysfunction in DCM remains challenging. Consequently, exploring additional therapeutic strategies for the prevention and treatment of DCM is urgently needed. Beyond pharmacological approaches, lifestyle modifications, particularly exercise and dietary interventions, play a fundamental role in managing DCM due to their significant cardiovascular benefits in diabetic patients. This review synthesizes recent advancements in the field, elucidating the underlying mechanisms through which exercise and dietary interventions influence DCM pathophysiology. By integrating these strategies, we aim to facilitate the development of personalized exercise and dietary regimens that effectively mitigate or prevent DCM progression. Graphical Abstract